The impact of wildfire on avian communities: exploring habitat associations two decades after fire - Vicini, Maria, author; Stevens-Rumann, Camille, advisor; Vogeler, Jody, committee member; Fornwalt, Paula, committee member (Colorado State University. Libraries, 2023)
Large high-severity wildfires have been affecting ponderosa pine dominated systems for decades, yet minimal long-term research has been conducted to address how avian species are responding to vegetation recovery and wildfire-driven conversion multiple decades after wildfire in ponderosa pine ecosystems of the southwestern United States. Understanding how community dynamics differ between low- and high-severity portions of burned footprints, and how vegetation structure relates to species presence is crucial for species conservation efforts, especially as wildfires in the western U.S. continue to have larger proportions of high-severity fire compared to historical fires. To address this in the Southwest, our study sought to quantify vegetation recovery, avian community dynamics across low- and high-severity sites, and quantify species-specific relationships with current vegetation structure in two post-fire footprints two decades after fire. This study focused on the Ponil Complex Fire in northern New Mexico and the Hayman Fire in southern Colorado, both of which burned in 2002. We found continued divergence between vegetation recovery at low- and high-severity sites, though this divergence was more pronounced at the Hayman Fire. We found also significant dissimilarities in avian community composition between low- and high-severity sites, and significantly lower species richness at high-severity sites across both wildfires. Forest-associated bird species presence was associated with more canopy cover and lower severity. Alternatively, lower canopy cover and higher severity were associated with the presence of a variety of grassland-, shrubland-, and desert-associated species. Our findings point to the importance of preserving pyrodiversity on the landscape to maximize suitable habitat for the greatest number of species, especially as it pertains to preserving adequate proportions of low-severity patches for forest-associated species who require intact canopy cover. However, large high-severity patches as the dominant component of the landscape will not support the most diverse array of bird communities 20+ years post fire.
Keywords: forest ecology; habitat ecology; wildfire ecology; forest science; avian conservation; wildfire